Technology adoption and contractual arrangements under credit constraints: evidence from apple growers in rural China - Deng, Hongtu; Duan, Yubing; Zhao, Yan (Frontiers in Sustainable Food Systems, 2025)
Sustainable agricultural transformation necessitates a synergistic evolution between the adoption of technology and institutional innovation. However, prevalent studies frequently regard technology as an exogenous tool, neglecting how its selection is constrained by resource endowments—especially access to credit—and how this subsequently alters contractual governance. Focusing on apple growers in rural China, this study examines how credit capacity affects the interplay between technology adoption and contractual arrangements. Through a comparative case study of three agribusinesses in Yiyuan County, Shandong Province, coupled with mathematical modeling and numerical simulations, we identify a causal chain linking credit capacity → technology choice → contractual adaptation. Key findings indicate: (1) Credit-constrained firms adopt labor-saving technologies incrementally, relying on high-monitoring-cost wage contracts that confine them to low-efficiency equilibria; (2) Firms with greater credit access implement integrated technologies (e.g., smart irrigation, virus-free seedlings, IoT systems) and transition to risk-sharing, incentive-compatible revenue-sharing contracts; (3) Deep technology embedding increases asset specificity and collaborative interdependence, driving endogenous shifts from hierarchical to cooperative governance. Mechanism analysis demonstrates that technology reduces uncertainty and reconfigures factor bargaining power, facilitating contractual adaptation. Policy implications underscore the necessity of activating land-use-right mortgages, cultivating endogenous rural financial systems, and encouraging contract innovations associated with technology services—crucial steps for the inclusion of smallholders in sustainable agri-value chains. This study offers micro-level evidence and a systemic framework for understanding the co-evolution of institutions and technology in agriculture within developing countries.